Bifurcaria bifurcata: a key macro‐alga as a source of bioactive compounds and functional ingredients. (24th May 2016) - Alves, Celso; Pinteus, Susete; Simões, Tiago; Horta, André; Silva, Joana; Tecelão, Carla; Pedrosa, Rui
Summary: The aim of this work was to study the proximate composition and the bioactive profile of Bifurcaria bifurcata . It contains 73.31 ± 0.69% of moisture, 8.57 ± 0.11 g per 100 g dry weight (d.w.) of protein, 5.81 ± 0.14 g per 100 g d.w. of lipid content and 30.15 ± 0.00 g per 100 g d.w. of ash. The polyunsaturated fatty acids were the most abundant fatty acid (FA), accounting for 2426.56 mg per 100 g which represents 41.77% of the total FA. The methanolic fraction showed high quantity of polyphenols (220.01 ± 0.010 phloroglucinol equivalents g −1 extract), DPPH radical reduction capacity (EC50 :58.82 μg mL −1 ) and oxygen radical absorbent capacity (3151.35 ± 119.33 μmol Trolox equivalents g −1 extract). The highest antimicrobial effect was observed against Pseudomonas aeruginosa (11.3 ± 1.5 mm) and Saccharomyces cerevisiae (IC50 :17.07 μg mL −1 ) induced by methanolic and dichloromethane fractions, respectively. Dichloromethane fraction revealed the highest antitumor activity on Caco‐2 and HepG‐2 cells. Bifurcaria bifurcata can be a promising source of bioactive compounds and functional ingredients. Abstract : Bifurcaria bifurcata showed to be a promissing source of new bioactive compounds with different biological activities (antioxidant, antimicrobial and antitumor) as well as source of new functional ingredients (Polyunsaturated fatty acids) according to regular food safety approvation.